Forest Cover – the Primary Guardian Against Climate Change and Biosphere Security - Basilashvili, Tsisana Z.; Janelidze, Magda G.; Basilashvili, Khatuna G. (Journals of Georgian Geophysical Society, 2025)
Due to ongoing global warming on our planet, the frequency of catastrophic natural disasters has increased, resulting in significant destruction and loss of life. In the 21st century, a further rise in temperature is expected, which will accelerate glacial melting, cause a sharp rise in sea levels, and lead to coastal flooding. Freshwater resources and agricultural productivity will decline. Desertification and other negative processes will intensify. Forest cover plays a critical role in climate regulation, oxygen balance stabilization, and biodiversity conservation. However, at present, widespread deforestation and forest fires are reducing forest areas worldwide, decreasing the process of photosynthesis. As a result, the excess thermal energy of solar radiation becomes a cause of global warming, reduced oxygen levels, and the emergence of new viral, bacterial, and chronic diseases. Today, to mitigate climate change and ensure the safety of the biosphere and the environment, all countries must pay special attention to the protection and expansion of forest cover. Everyone must contribute to forest restoration and afforestation. In agricultural fields, protective forest belts should be planted to help increase crop yields.